THE STRENGTHENING WOMEN-LED MSMEs IN BANTEN PROVINCE: DIGITAL TRANSFORMATION, FINANCIAL INCLUSION, AND LOCAL ECONOMIC RESILIENCE - Icin Quraysin (Prosiding Amal Insani Foundation, 2026)
Micro, Small, and Medium Enterprises (MSMEs) led by women constitute a fundamental pillar of inclusive economic growth in Indonesia, particularly in Banten Province. This study analyzes the strategic contribution of women-led MSMEs in strengthening local economic resilience and examines how digital transformation and financial inclusion serve as key drivers of sustainable development. Despite their significant contribution to job creation, poverty reduction, and household income stabilization, women entrepreneurs continue to face structural challenges, including limited access to formal financing, low levels of digital literacy, restricted managerial capacity, and minimal integration into formal value chains. This research employs a descriptive qualitative approach through a literature review and secondary data analysis derived from national statistical publications and international development reports. The findings indicate that digital transformation—through the adoption of e-commerce platforms, social media marketing, fintech services, and QR-based payment systems—enhances operational efficiency, financial transparency, and market reach. Furthermore, financial inclusion initiatives significantly reduce vulnerability to economic shocks and improve business sustainability. This study proposes an integrated empowerment framework that combines digital capacity building, inclusive financing policies, institutional mentoring, and cross-sector collaboration. Strengthening women-led MSMEs should be positioned not only as an economic policy priority but also as a strategic instrument for gender equality, poverty alleviation, and long-term regional resilience.